The Development of Healthcare Model and Memory Rehabilitation of Elderly with Dementia by Using Community-based Participation - Opas, Pitchaporn; Arunsirot , Nutreutai; Pattarawongthana, Jarunee; Boonyarittanon‬‬‬‬, Ninooch (Community and Social Development Journal, 2025)
This research aimed to develop a healthcare model and memory rehabilitation of the elderly with dementia by using community-based participation and to examine the satisfaction of the participating elderly towards the healthcare model and memory rehabilitation. The population in this research was the elderly people, whose age was 60 years and over, living in Nong Phueng, Yang Noeng and Saraphi subdistrict municipalities, Chiang Mai province. The purposive sampling method was applied to select the sample group of 100 male and female elderly people. The data collection instruments comprised a structured interview about dementia and community contexts, a focus group discussion, Thai Mental State Examination (TMSE), and a satisfaction questionnaire for the elderly. The data were statistically analyzed using mean and standard deviation. The results showed that the healthcare model and memory rehabilitation of the elderly with dementia by using community-based participation was developed. It was composed of three phases, including community preparation phase, research phase, and post-research phase. Furthermore, the questionnaire results revealed that the overall satisfaction of the participating elderly was at a high level, with the mean of 4.46 ( 0.52).